THE SIGNIFICANCE OF THE COMBINED USE OF THE TI-RADS SYSTEM, ELASTOGRAPHY AND FINE NEEDLE ASPIRATION BIOPSY IN THE DIAGNOSIS AND TREATMENT TACTICS IN THYROID NODULES - Hummatov, A.F.; Aliyev, S.A. (World of Medicine and Biology, 2023)
The results of examination and treatment of 399 patients aged 12 to 83 years with thyroid nodules of various morphological structures were analyzed. All patients were ranked into 2 groups. Group 1 included 127 (37.6 %) patients who underwent a fine needle aspiration biopsy of thyroid nodules. The 2nd group included 212 (62.4 %) patients who underwent ultrasound examination using the TI-RADS system, sonoelastography in combination with fine needle aspiration biopsy. Surgical treatment was performed in 50 (group 1) (39.3 %) of 127 patients, benign tumors were diagnosed in 40 (80 %), malignant tumors in 10 (20 %). Surgical treatment in group 2 was performed in 52 (24.5 %) of 212 patients, benign tumors were detected in 33 (63.5 %) patients, malignant in 19 (36.5 %). The combined use of the TI-RADS system, sonoelastography and fine needle aspiration biopsy contributed to a significant increase in the frequency of detection of thyroid nodules of malignant structure, which amounted to 36.5 % in patients of the main group (versus 20 % in patients of the control group) and a decrease in the frequency of surgical interventions by more than 1.5 times in patients of the second group.